Incidencia de Mycobacterium bovis en la ganadería bovina de la FACIAG de la Universidad Técnica de Babahoyo - Alcívar Chalco, Brithanny Aylin (2024)
Bovine tuberculosis is a disease that seriously affects livestock farms and reduces the production and marketing of their products. Likewise, the infection can present itself as a zoonosis, causing real difficulties for human health. The type of research applied was evaluative and descriptive using the chi-square test, where the results obtained on the Incidence of Mycobacterium bovis were evaluated. The entire bovine population of the Agricultural Science Faculty was considered for this experimental work, with a total of 74 existing animals, to determine the incidence and its relationship with the independent variables such as; sex, age, racial group that incident with the presence of the disease. Of the 74 cases investigated, 0 cases are positive and 74 are negative, which represents 0% positive through the tuberculization technique in the anus-caudal internal fold. Depending on sex, an almost equal animal population was found between females and males, with females having a higher percentage with 52.70%. It was calculated that 60% corresponds to ages over 24 months, however, it was contacted that of that group 37.83% corresponds to the category of steers. The absence of positive cases in the study confirms the effectiveness of current surveillance and management strategies in the livestock area. Epidemiological surveillance, constant monitoring, is essential to maintain the state of absence of the disease.